Day-to-day dynamics of fetal heart rate variability to detect chorioamnionitis in preterm premature rupture of membranes - Aline Taoum; Guy Carrault; Caroline Tesson; Maxime Esvan; Bruno Laviolle; Linda Lassel (PLoS ONE, 2025)
Background Chorioamnionitis is recognized as a major consequence of preterm premature rupture of membranes (PPROM), and a frequent cause of neonatal morbidity and mortality. The association between fetal heart rate (FHR) and chorioamnionitis remains unclear. Objectives The aim of this study was to evaluate the dynamics of FHR in a PPROM population at the approach of delivery according to the presence or absence of chorioamnionitis. Materials & methods 120 pregnant women with PPROM between 26 and 34 weeks’ gestation were enrolled in this multicenter prospective unblinded study. All participants were fully informed of the study’s objectives. 39 of the 120 patients were included in the analysis of FHR recordings. The analysis consisted of extracting features from computerized FHR analysis (cFHR) and fetal heart rate variability analysis (FHRV) in the temporal, frequency and nonlinear domains. Then, each set of features was analyzed separately using the multiple factor analysis, where three groups were defined as the feature set for days 0, -1 and -2 prior to birth. The distances between the global projection and the projections for each day were computed and used in the ROC analysis to distinguish chorioamnionitis from non-chorioamnionitis group. Results The results showed that there were significant differences in certain features between populations with and without chorioamnionitis. The distinction between the two populations reached an area under the curve (AUC) of only 37% [34–40] for cFHR features and 63% [59–66] for time-domain FHRV features when comparing all stages of chorioamnionitis to non-chorioamnionitis subjects. When only stage 3 chorioamnionitis was compared to non-chorioamnionitis patients, the AUC reached 90% [88–93] for nonlinear-domain and 84% [82–87] for time-domain FHRV features, whereas it was limited to 71% [68–74] using cFHR features. Conclusion The present study suggests that the HRV features are more reliable for diagnosing chorioamnionitis than cFHR, and that the assessment of features dynamics over several days is an interesting tool for detecting chorioamnionitis. Further study should be carried out on a larger sample to confirm these findings, improve the diagnostic performance of chorioamnionitis and help clinicians decide on delivery criteria.